2021
DOI: 10.1177/10105395211051237
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Four or More Antenatal Care Visits Among Working Women in Indonesia

Abstract: This study aimed to analyze the determinants of 4 or more antenatal care (ANC) visits among working women in Indonesia. The researchers extracted data from the Indonesian Demographic and Health Survey 2017 and obtained a sample size of 8239 working women aged between 15 and 49 years. Women’s residence, age, marital status, education level, parity, economic status, and health insurance were selected as the independent variables. Binary logistic regression was used for the analysis. Older working women, married … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 49 publications
4
22
1
1
Order By: Relevance
“…In addition, the workplace usually facilitates workers with health insurance. 4 , 33 The study results show similarities with previous studies that work influences NHI membership. 24 …”
Section: Discussionsupporting
confidence: 86%
“…In addition, the workplace usually facilitates workers with health insurance. 4 , 33 The study results show similarities with previous studies that work influences NHI membership. 24 …”
Section: Discussionsupporting
confidence: 86%
“…Women from the richest households had significantly more ANC visits than women from the poorest households. In line with this finding, studies from Bangladesh [ 29 ] and Indonesia [ 30 ] found that women from the wealthiest families were more likely to receive optimal ANC services than women from poorer families. This might be the improvement of the economy helps to advance health care utilization and able to afford medical and non-medical costs associated with ANC service during pregnancy [ 31 34 ].…”
Section: Discussionmentioning
confidence: 60%
“…Similar to previous studies, it reported that someone who works has a higher odds than someone who does not work to take advantage of hospital services [ 44 , 51 ]. Work is related to income and purchasing power, and people who have jobs have sources of revenue, and the existence of payment makes it easier for someone to take advantage of the health services needed [ 52 ].…”
Section: Discussionmentioning
confidence: 99%